Co-expression Analysis of Sirtuins and Related Metabolic Biomarkers in Juveniles of Gilthead Sea Bream (Sparus aurata) With Differences in Growth Performance - Simó-Mirabet, Paula; Perera, Erick; Calduch-Giner, Josep A.; Afonso, Juan M.; Pérez-Sánchez, Jaume (Frontiers in Physiology, 2018)
Sirtuins (SIRTs) represent a conserved protein family of deacetylases that act as master regulators of metabolism, but little is known about their roles in fish and livestock animals in general. The present study aimed to assess the value of SIRTs for the metabolic phenotyping of fish by assessing their co-expression with a wide-representation of markers of energy and lipid metabolism and intestinal function and health in two genetically different gilthead sea bream strains with differences in growth performance. Fish from the fast-growing strain exhibited higher feed intake, feed efficiency and plasma IGF-I levels, along with higher hepatosomatic index and lower mesenteric fat (lean phenotype). These observations suggest differences in tissue energy partitioning with an increased flux of fatty acids from adipose tissue towards the liver. The resulting increased risk of hepatic steatosis may be counteracted in the liver by reduced lipogenesis and enhanced triglyceride catabolism, in combination with a higher and more efficient oxidative metabolism in white skeletal muscle. These effects were supported by co-regulated changes in the expression profile of SIRTs (liver, sirt1; skeletal muscle, sirt2; adipose tissue, sirt5-6) and markers of oxidative metabolism (pgc1α, cpt1a, cs, nd2, cox1), mitochondrial respiration uncoupling (ucp3) and fatty acid and triglyceride metabolism (pparα, pparγ, elovl5, scd1a, lpl, atgl) that were specific to each strain and tissue. The anterior intestine of the fast-growing strain was better suited to cope with improved growth by increased expression of markers of nutrient absorption (fabp2), epithelial barrier integrity (cdh1, cdh17) and immunity (il1β, cd8b, lgals1, lgals8, sIgT, mIgT), which were correlated with low expression levels of sirt4 and markers of fatty acid oxidation (cpt1a). In the posterior intestine, the fast-growing strain showed a consistent up-regulation of sirt2, sirt3, sirt5 and sirt7 concurrently with increased expression levels of markers of cell proliferation (pcna), oxidative metabolism (nd2) and immunity (sIgT, mIgT). Together, these findings indicate that SIRTs may play different roles in the regulation of metabolism, inflammatory tone and growth in farmed fish, arising as powerful biomarkers for a reliable metabolic phenotyping of fish at the tissue-specific level.